Duch d’Hondta w Strasburgu. Zasada proporcjonalnej dystrybucji stanowisk w Parlamencie Europejskim - Kirpsza, Adam (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
Proportionality is an intrinsic feature of parliamentary democracy. It is a principle stating that, depending on its size, each political party has a commensurate ability to influence legislature. This is confirmed by comparative studies which show that proportionality is a significant principle in the distribution of parliamentary posts in a majority of West European states. Consequently, even deputies from the smallest parties can chair commissions or lead sessions of the chambers, and by this token participate in the political decision-making process. This softens the domination of the majority party and – in line with Arend Lijphart’s concept – generates consensual democracy, based on the search for broad compromises instead of simply outvoting the opponent. Given this picture, a question emerges whether the situation is similar in the representative institution of the European Union, i.e. the European Parliament. The paper answers this question positively. The standard of proportionality has strong roots in the European Parliament forming a fundamental principle expressed in terms of d’Hondt’s formula applied to distribute posts among different political groups. This mainly concerns the division of the members of the Presidium and commission chairmen, who exercise the most important decisive functions. The implementation of the idea of appropriate representation may not be ideal, but divergences are rare, insignificant and usually they result from political bargaining that favors smaller fractions. The proportionality principle is also binding when distributing parliamentary posts inside political groups. There is a strong and positive correlation between the size of national delegations and the number of key posts they obtain in the Parliament – members of the Presidium, commission chairmen and coordinators. Only in the case of the latter is proportionality subjected to certain distortions, following from their key political importance. This, however, does not interfere with the general picture of symmetric participation of national groups in appointing parliamentary posts. In conclusion, the standard of proportionality allows all political groups to adequately participate in the work of the European Parliament, which deserves to be emphasized, the more so, as it is not formalized.
D’Hondt’s spirit in Strasbourg. The principle of proportional distribution of posts in the European Parliament